2015
DOI: 10.1002/2014ja020938
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation of the interaction of solar wind protons with a concentrated lunar magnetic anomaly

Abstract: Using a two-dimensional hybrid simulation, we study the physics of the interaction of the solar wind with a localized magnetic field concentration, or "magcon," on the Moon. Our simulation treats the solar wind protons kinetically and the electrons as a charge-neutralizing fluid. This approach is necessary because the characteristic scale of the magcon is of the same order or smaller than the proton inertial length-the characteristic scale in the hybrid simulation. Specifically, we consider a case in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
1
16
1
Order By: Relevance
“…There is no significant shift of the observed spectra toward lower energies compared to the model results. Thus, we do not see any indication of a deceleration by hundreds of eV of the incident ions by electric fields such as those observed at the Moon in the solar wind by e.g., Saito et al [2012] and Futaana et al [2013], modeled by several recent studies [e.g., Poppe et al, 2012;Kallio et al, 2012;Jarvinen et al, 2014;Deca et al, 2014Deca et al, , 2015Fatemi et al, 2015;Giacalone and Hood, 2015;Zimmerman et al, 2015], and observed in laboratory [e.g., Bamford et al, 2012;Howes et al, 2015;Wang et al, 2012Wang et al, , 2013. Notably, most of the cited studies concern primarily the low solar zenith angle case, while the case we observe in P1 is at high solar zenith angles.…”
Section: 1002/2015ja021826contrasting
confidence: 45%
“…There is no significant shift of the observed spectra toward lower energies compared to the model results. Thus, we do not see any indication of a deceleration by hundreds of eV of the incident ions by electric fields such as those observed at the Moon in the solar wind by e.g., Saito et al [2012] and Futaana et al [2013], modeled by several recent studies [e.g., Poppe et al, 2012;Kallio et al, 2012;Jarvinen et al, 2014;Deca et al, 2014Deca et al, , 2015Fatemi et al, 2015;Giacalone and Hood, 2015;Zimmerman et al, 2015], and observed in laboratory [e.g., Bamford et al, 2012;Howes et al, 2015;Wang et al, 2012Wang et al, , 2013. Notably, most of the cited studies concern primarily the low solar zenith angle case, while the case we observe in P1 is at high solar zenith angles.…”
Section: 1002/2015ja021826contrasting
confidence: 45%
“…Roughly speaking, portions of the surface with open magnetic field lines may be expected to experience normal or even accelerated solar wind‐related space weathering, leading to darkening, whereas portions of the surface beneath closed magnetic field lines should experience greater protection from solar wind weathering, thus remaining relatively bright (Hemingway & Garrick‐Bethell, ). Indeed, magnetometer‐based studies of magnetic field structure (Hemingway & Garrick‐Bethell, ; Shibuya et al, ; Tsunakawa et al, ), as well as hybrid and kinetic plasma simulations (e.g., Bamford et al, , ; Deca et al, , ; Fatemi et al, ; Giacalone & Hood, ; Jarvinen et al, ; Poppe et al, , ; Zimmerman et al, ), indicate that swirl morphology may be dictated by magnetic field topology in precisely this way. It has also been proposed that swirls may be the result of electrostatic (Garrick‐Bethell et al, ) or magnetic (Pieters et al, ) sorting of fine‐grained materials, rather than of deflection of solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have explored the potential mechanisms at work within crustal magnetic anomalies with laboratory experiments [ Wang et al , , ] and numerical simulations, including magnetohydrodynamic (MHD) [e.g., Harnett and Winglee , , ; Xie et al , ], hybrid [ Fatemi et al , , ; Jarvinen et al , ; Giacalone and Hood , ; Poppe et al , ], and kinetic/particle‐in‐cell methodologies [e.g., Poppe et al , ; Deca et al , , ; Zimmerman et al , ; Bamford et al , ]. These simulations have suggested that large‐scale ambipolar and/or Hall electrostatic fields may be the primary mechanism of proton reflection from lunar crustal magnetic fields, rather than magnetic reflection.…”
Section: Introductionmentioning
confidence: 99%